The Effect of Temperature on the Rate of Chemical Reactions (Texas Journal of Engineering and Technology, 2022)
Chemical reactions occur at different rates. Some of them happen in a thousandth of a second, while others happen in minutes, hours, days, months and years. It is also known that such reactions can occur quickly and slowly, depending on the conditions, for example, they can be rapid at high temperatures and slow at cold temperatures. The difference between the rates of these reactions can be large. The following article is devoted to the study of the effect of temperature on the rate of chemical reactions.